Do quilombo à universidade: as escrevivências de formação de uma educadora matemática nos afazeres decoloniais da extensão universitária - CHAVES, Amanda da Costa (2023)
The work, presented and organized in the format of an academic portfólio, highlights the scientific productions carried out, by the author, during her participation, as a grantee, in the Projeto de Extensão Ludicidade Africana e Afro-Brasileira (LAAB), linked to the Faculty of Pedagogy of the Campus of Castanhal. Among the various actions carried out in the project, we present those related to the ethnic and racial quests in the teaching and learning of mathematics, with a focus on the content of basic operations, rational and natural numbers, mathematical logic in probability and explorations of geometric transformations. These items are presented in three texts developed during two years from 2018 to 2022, which coincide with the permanence in the extension bag and the graduation in the Bachelor of Mathematics. The three articles are submitted to academic events in the area of education, being approved, presented in oral communication format and published, in full, in our annais of the event and in ebooks. The first text was constituted in an experience report with the game Li'bel Merafib, in 2nd and 5th year classes, analyzing the development of numerical, strategic and logical-mathematical thinking, being a result of extension practices in public schools of Ensino Fundamental. The second text presents reflections on the recreational and mathematical activities developed by the LAAB project, from 2012 to 2019, highlighting the actions carried out in quilombola communities and the training for students of the UFPA Castanhal Campus. In the third publication, it turns to the training of teachers who teach mathematics, presenting to the office of recreational and cultural training, carried out remotely, during the COVID-19 pandemic, focused on symmetry counts through the analysis of standards and African cultural practices, especially the traces and points called sona. Likewise, the articles represent three types of audiences and activities developed in the LAAB project and show the great contribution of his experience as an extension scholar to think and do a culturally significant mathematical education for black and quilombola communities, and to rethink, in Critical and anti-racist bases, the relationship between Culture and Mathematics Education.